Chemical attributes of soil in agroforestry systems is conditioned by the management system adopted (Research, Society and Development, 2020)
The aim of this study was to evaluate the influence of vegetation management on soil chemical attributes during the implementation of an agroforestry system in Pará, Brazil. Three treatments were evaluated - T1 Control (secondary vegetation - SF), T2 - Fire management system (FMS) and T3 - Management system without vegetation burning (MSWB). Soil samples were collected at 30 cm deep to analyze chemical attributes. The data were analyzed using Analysis of Variance - ANOVA, and the t-test. Treatment T2 caused the most changes in soil chemical attributes on the first analysis showing increased pH, increased levels of N, P, K, Ca, Sum of bases, CEC and percentage of base saturation, and decreased potential acidity of Al in the short term. However, in the second evaluations 48 months later, there was an inversion, in which a reduction of pH, the contents of N, P, K, Ca, Sum of bases and percentage of base saturation, as well as increased potential acidity and of the contents of Al of the soil were observed. For treatments T1 and T3, there were no substantial soil attributes changes during the first and second evaluations. Thus, soil chemical attributes were altered according to the type of management of secondary vegetation and evaluation period during the implementation of Agroforestry Systems.